Climate shapes community flowering periods across biomes - Ruby E. Stephens; Hervé Sauquet; Greg R. Guerin; Mingkai Jiang; Daniel Falster; Rachael V. Gallagher (Journal of Biogeography, 2022)
Aim Climate shapes the composition and function of plant communities globally, but it remains unclear how this influence extends to floral traits. Flowering phenology, or the time period in which a species flowers, has well‐studied relationships with climatic signals at the species level but has rarely been explored at a cross‐community and continental scale. Here, we characterise the distribution of flowering periods (months of flowering) across continental plant communities encompassing six biomes, and determine the influence of climate on community flowering period lengths. Location Australia. Taxon Flowering plants. Methods We combined plant composition and abundance data from 629 standardised floristic surveys (AusPlots) with data on flowering period from the AusTraits database and additional primary literature for 2983 species. We assessed abundance‐weighted community mean flowering periods across biomes and tested their relationship with climatic annual means and the predictability of climate conditions using regression models. Results Combined, temperature and precipitation (annual mean and predictability) explain 29% of variation in continental community flowering period. Plant communities with higher mean temperatures and lower mean precipitation have longer mean flowering periods. Moreover, plant communities in climates with predictable temperatures and, to a lesser extent, predictable precipitation have shorter mean flowering periods. Flowering period varies by biome, being longest in deserts and shortest in alpine and montane communities. For instance, desert communities experience low and unpredictable precipitation and high, unpredictable temperatures and have longer mean flowering periods, with desert species typically flowering at any time of year in response to rain. Main conclusions Current climate conditions shape flowering periods across biomes, with implications for phenology under climate change. Shifts in flowering periods across climatic gradients reflect changes in plant strategies, affecting patterns of plant growth and reproduction as well as the availability of floral resources for pollinators across the landscape.

Marine latitudinal diversity gradients, niche conservatism and out of the tropics and Arctic: Climatic sensitivity of small organisms - Wing‐Tung Ruby Chiu; Moriaki Yasuhara; Thomas M. Cronin; Gene Hunt; Laura Gemery; Chih‐Lin Wei (Journal of Biogeography, 2020)
Aim The latitudinal diversity gradient (LDG) is a consequence of evolutionary and ecological mechanisms acting over long history, and thus is best investigated with organisms that have rich fossil records. However, combined neontological‐palaeontological investigations are mostly limited to large, shelled invertebrates, which keeps our mechanistic understanding of LDGs in its infancy. This paper aims to describe the modern meiobenthic ostracod LDG and to explore the possible controlling factors and the evolutionary mechanisms of this large‐scale biodiversity pattern. Location Present‐day Western North Atlantic. Taxon Ostracoda. Methods We compiled ostracod census data from shallow‐marine environments of the western North Atlantic Ocean. Using these data, we documented the marine LDG with multiple metrics of alpha, beta (nestedness and turnover) and gamma diversity, and we tested whether macroecological patterns could be governed by different environmental factors, including temperature, salinity, dissolved oxygen, pH and primary productivity. We also explored the geologic age distribution of ostracod genera to investigate the evolutionary mechanisms underpinning the LDG. Results Our results show that temperature and climatic niche conservatism are important in setting LDGs of these small, poorly dispersing organisms. We also found evidence for some dispersal‐driven spatial dynamics in the ostracod LDG. Compared to patterns observed in marine bivalves, however, dispersal dynamics were weaker and they were bi‐directional, rather than following the ‘out‐of‐the‐tropics’ model. Main conclusions Our detailed analyses revealed that meiobenthic organisms, which comprise two‐thirds of marine diversity, do not always follow the same rules as larger, better‐studied organisms. Our findings suggest that the understudied majority of biodiversity may be more sensitive to climate than well‐studied, large organisms. This implies that the impacts of ongoing Anthropocene climatic change on marine ecosystems may be much more serious than presently thought.

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. II. The vascular flora - Rhett D. Harrison; Roy Banka; Ian W. B. Thornton; Mike Shanahan; Ruby Yamuna (Journal of Biogeography, 2001)

Colonization of an island volcano, Long Island, Papua New Guinea, and an emergent island, Motmot, in its caldera lake. II. The vascular flora - Rhett D. Harrison; Roy Banka; Ian W. B. Thornton; Mike Shanahan; Ruby Yamuna (Journal of Biogeography, 2001)
Aim Long Island erupted catastrophically in c . 1645 with the probable destruction of its entire biota. While several expeditions have visited the island since, no survey of its flora has been published. In 1968 a small island, Motmot, emerged from its caldera lake. Motmot has been surveyed several times but not since 1988. The aim of this study was to investigate the colonization by vascular plants of this interesting nested pair of islands. Location Long Island is 55 km off the northeast coast of Papua New Guinea (PNG) and Motmot lies in its fresh water caldera lake, Lake Wisdom, c . 4 km from the rim of the surrounding volcano. Methods We conducted a complete survey of the vascular plants on Motmot and made ad hoc collections on Long Island, including surveying three small plots, over 15 days in 1999. In addition, we incorporated data from several collections lodged at the regional herbarium in Lae. Data on seed dispersal syndromes and plant habit were obtained from the literature. Results We recorded 305 species of vascular plants from Long Island, but most trees were small and the species diversity was low. Motmot was still very sparsely vegetated and only forty‐five species of vascular plants were found. Communities on Motmot were unspecialized and common species widespread. The flora of Motmot was not significantly different from that on Long Island in terms of the number of species amongst higher taxa, seed dispersal syndromes or plant habits. Main conclusions Low rainfall combined with very porous soils may be responsible for the small stature and low diversity of the forest on Long Island's caldera rim. The absence of specialist littoral species on Motmot, as a result of its landlocked situation, is probably responsible for the very slow species recruitment on the island. This community appears to be functionally important for colonization by comparison with other small volcanic islands in a marine situation.